Rome adventure [videorecording (DVD)] - Daves, Delmer, 1904-1977; Donahue, Troy, 1936-2001; Dickinson, Angie; Brazzi, Rossano, 1916-1994; Pleshette, Suzanne, 1937-2008 (Distributed by Warner Home Video, 2009)
Tired of stuffy New England, Prudence Bell longs for a Rome adventure. She heads for the Eternal City and encounters a handsome student, a dashing older man, and competition from a wily woman of the world.